IMPLEMENTASI PROFIL PELAJAR PANCASILA DI MTSN 1 KOTA MALANG - Aisyah Agustin Wahyudi; Muhammad Miftahusyai'an (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Character education is the foremost guard in shaping the character of students. However, because character education at this time has begun to fade and the values of Pancasila are rarely practiced in everyday life. Especially related to the phenomenon of intolerance that is rife in the world of education lately as well as the occurrence of bullying and threats of radicalism. Therefore, it is necessary to improve in terms of inculcating an attitude of tolerance in students, especially the younger generation. The focus of the research in this study is how to cultivate an attitude of tolerance in students at MTsN 1 Malang City through the Pancasila Student Profile. The approach used is descriptive type. The data collection technique uses observation, interview and documentation techniques, with sources namely school principals, social studies teachers, PPkn teachers, head of class 8M and chairman of the student council. The results of the study indicate that in an effort to inculcate an attitude of tolerance through the Pancasila Student Profile, the following activities are carried out in the first point. Have faith, fear God Almighty and have noble character, make it a habit to oblige students to pray in congregation which includes dhuha prayer, dhuhur prayer, asr prayer, and Friday prayer. The second point of Independence is the application of the SKS System. Furthermore, Critical Reasoning with the KIR class (Adolescent Scientific Work). Be creative by making art from used items such as used bottles, plates, tote bags, cardboard and other used items. Fifth, Global Diversity with the existence of a student exchange program. Lastly, Gotong Royong, there is community service for non-osis and student council members and there are social service activities carried out by students from one of the 8M grades. While the obstacles are caused by internal factors or within students and external factors, namely the covid-19 pandemic. The solution is to always be guided and control the students so that they have a high tolerance attitude. The role of parents and teachers is very important in working together in inculcating an attitude of tolerance and global diversity in students.